The nexus between technology innovation and CO2 emissions in Malaysia: Evidence from granger causality test - Kwang, Jing Yii; Caroline Geetha (Elsevier BV, 2017)
This study mainly aims to examine the causal relationship between technology innovation and CO2 emissions with economic growth, electricity consumption and energy price in Malaysia. The data over period of 1971 to 2013 is analyzed by employing VECM and TYDL granger causality tests. The results indicate that technology innovation is negatively related to CO 2 emissions in short run while no long run relationship found. The VECM granger causality shows that technology innovation granger cause CO 2 emissions in short run. Meanwhile there is no causal effect found in long run from TYDL granger causality. Therefore, policymakers should promote the innovation research without any postponement for the sake of economic development and environmental sustainability.